Physico-Chemical Analysis of Sugar Mill Effluent, Contaminated Soil and its Effect on Seed Germination of Paddy (Oryza sativa L.) - Samuel, Sajani (International Journal of Pharmaceutical & Biological Archive, 2011)
Sugar mills play a major role in polluting the water bodies and land by discharging a large amount of wastewater as effluent. The sugar mill effluents are having high amount of suspended solids, dissolved solids, BOD, COD, chloride, sulphate, nitrates, calcium and magnesium. The continuous use of these effluents harmfully affects the crops when used for irrigation. In the present study, physico-chemical parameters of sugar mill effluent and contaminated soil was determined and the effect of various concentrations (0%, 10%, 25%, 50%, 75 % and 100%) of the effluent on seed germination, germination speed of Paddy (Oryza sativa L.) was also studied. The low effluent pH (4.20), total dissolved solids, (TDS, 1480mg/L) and chemical oxygen demand, (COD, 3140mg/L) indicate the high inorganic and organic content with an acidic load. Germination percentages and germination values decrease with increasing concentration of effluent in the seeds tested.